Avaliação retrospectiva de pacientes com leucoplasia oral - Paulo, Luiz Fernando Barbosa de (2011)
Leukoplakia is defined as a white lesion that is not removed by scraping and cannot be classified as any lesion, beyond it is not representing histopathological entity, because it can represent many epithelial maturation riots. The annual percentage of malignant transformation varies in different parts of the world, probably as a result of differences in tobacco and dietary habits. This work makes a retrospective, observational study in 76 patients who had been diagnosed with leukoplakia in the period 1996 to 2010 and with a minimum follow-up period of 12 months. Analysis of the sample showed no gender predilection, mean age 60.3 years and mean follow-up of 7.4 years. Smoking was found in 78% of patients. The new clinical evaluation showed that 18.7% of lesions disappeared, 31.2% did not change in size or appearance, 21.8% showed increase in the size or appearance, 3.1% showed a substantial regression of the lesion and 15,6% suffered malignant transformation. Among the patients who showed increase or appearance of lesions in other sites, 100% of them reported smoking in an average time of 32.5 years. Finally, in the five lesions that had undergone malignant transformation, 80% of them were present in smokers by an average of 35.5 years. Therefore, it is clear that the persistence of smoking is an important factor for the appearance of new lesions and malignant transformation of leukoplakia.